Analysis on the Impact of Limited In-Person Classes in Higher Education Institution Students Towards Psychosocial Support - Aquino, John Michael D.; Simbre, Abegail P. (International Journal of Multidisciplinary Sciences, 2025)
This study explored the impact of transitioning from distance learning modality to limited in-person classes to students in a higher education institution in the Philippines had caused psychological impact to working students in a tertiary institution. Ten working students were chosen purposively to participate in this phenomenological study. They were breadwinners in their families and claimed they were psychologically impacted by the transitions brought about by the pandemic because of the emotional distress and anxiety. The data was gathered through interviews with a validated interview guide from field experts and was analyzed using thematic analysis. Researchers also considered ethical considerations in conducting research for participants. The results revealed that participants experienced varied impacts, particularly in adjusting their daily routines, facing technological and financial challenges, managing stress in physical, psychological, and mental aspects, and adapting to socialization and communication changes. Despite these challenges, they expressed increased adaptability and resilience, maintaining positive attitudes and aspirations to continue learning. Effective time management, adjustments to learning modalities, and clear policies were identified as key factors that could have eased their transition. The study recommends that students should fully commit to balancing both work and study. Higher education institutions (HEIs) can support them by providing psychological assistance, flexible learning options, academic guidance, wellness programs, financial aid, and partnerships with local businesses to help them sustain their education while working.